Teaching principles of microeconomics - Maier, Mark W. (Mark Warner), 1961-; Ruder, Phil (Elgar guides to teaching, 2023)
"Abundant with practical advice and ready-to-use teaching examples, this dynamic guide will help both new and experienced instructors of Principles of Microeconomics to reconsider and refine their courses. Mark Maier and Phil Ruder assemble the wisdom of 25 eminent scholars of economic education on how best to introduce students to the discipline and inspire a long-lasting passion for microeconomics. Beyond offering guidance to educators on how to improve students' learning experience, the book proposes measures for addressing many of the vexing challenges that face the economics discipline today. Chapters provide suggestions on how to capture students' attention and ensure their continued engagement, including selecting course content that focuses on important public policy topics and pressing issues within modern society, adopting evidence-based pedagogical strategies in the classroom and online, and tackling issues of diversity, equity, and inclusion within the discipline. The ideas advanced in this illuminating guide highlight the possibility of continued improvement throughout one's teaching career. The jargon-free advice in this insightful teaching guide will also be of interest to deans, teaching and learning center directors, and other administrators of undergraduate institutions"--